Delaminación en modos combinados I/II para componentes de fibra de vidrio bajo cargas cuasi estáticas : un análisis analítico y computacional (2017)
"The increasing use of composite materials has motivated scientists to understand how their delamination process occurs which is one of the most frequent failure modes in laminated composites. The mixed mode bending (MMB) test configuration was developed combining double cantilever beam (DCB) mode I loading and end-notch flexure (ENF) mode II loading. The energy release rate was calculated using beam theory. In order to validate the results obtained analytically a finite element analysis was done to calculate GI for mode I and GII for mode II. The simulation of delamination was developed by virtual crack closure technique (VCCT) in ANSYS APDL." -- Tomado del Formato de Documento de Grado.